48 Correlation of left ventricular myocardial work indices and invasive measurement of stroke work. (8th December 2021) - Landra, Federico; Mandoli, Giulia Elena; Chiantini, Benedetta; Barilli, Maria; Merello, Giacomo; De Carli, Giuseppe; Sciaccaluga, Carlotta; Lisi, Matteo; Focardi, Marta; D'Ascenzi, Flavio; Fineschi, Massimo; Iadanza, Alessandro; et al.
Abstract: Aims: A novel echocardiographic method allows to non-invasively assess myocardial work using pressure–strain loops. Even though left ventricular myocardial work has already emerged as a promising prognostic tool for various pathological conditions, its relationship with invasively-derived corresponding indices has not been assessed in humans yet. This study aimed to explore the correlation between left ventricular myocardial work (LVMW) indices and invasively derived left ventricular stroke work index (LVSWI) in a cohort of patients with advanced heart failure (HF) considered for heart transplantation. Methods and results: All consecutive patients with advanced heart failure considered for heart transplantation from 2016 to 2021 that had already performed right heart catheterization (RHC) as part of the workup and with an available echocardiographic exam were included ( n  = 91). Myocardial work analysis was performed in 44 patients, according to exclusion criteria. Conventional LV functional parameters and LVMW indices, including LV global work index (LVGWI), LV global constructive work (LVGCW), LV global wasted work (LVGWW), LV global work efficiency (LVGWE), and other were calculated and compared with invasively measured LV stroke work index (LVSWI). Median age was 60 years [interquartile range (IQR): 54–63]. Median time between RHC and echocardiography was 0 months (IQR: 0–1). For the most part, etiology of HF was non-ischaemic (61.4%) and all patients were either on class NYHA II (61.4%) or III (27.3%). Median left ventricular ejection fraction was 25% (IQR: 22.3–32.3), median NT-proBNP 1377 pg/ml (IQR: 646–2570). Among conventional parameters of LV function, LVEF did not significantly correlate with LVSWI ( r  = 0.308; P  = 0.050) whereas LV global longitudinal strain (LVGLS) did ( r  = −0.337; P  = 0.031). With regard to LVMW indices, some of them demonstrated correlation with LVSWI, particularly LVGWI ( r  = 0.425; P  = 0.006), LVGCW ( r  = 0.506; P  = 0.001), LV global positive work (LVGPW; r  = 0.464; P  = 0.003), and LV global systolic constructive work (LVGSCW; r  = 0.471; P  = 0.002). Conclusions: Among left ventricular myocardial work indices, LVGCW correlated better with invasively derived stroke work, thus representing a powerful and reliable tool for a more comprehensive evaluation of myocardial function.